The effect of aluminium on plant growth and its amelioration in acid subsoils of the Western Cape - Kotze, W. A. G.(Willem Adriaan Gysbert) (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD(Agric))-University of Stellenbosch, 1974.